Assessment of brain atrophy as a promising marker of radiological activity in patients with relapsing–remitting multiple sclerosis - Pogoda-Wesołowska, Aleksandra; Stachura, Ignacy; Szukało, Piotr; Wieczorek, Maria; Stępień, Adam (Frontiers in Neuroscience, 2025)
IntroductionThe measurement of brain atrophy in patients with relapsing–remitting multiple sclerosis (RRMS) may be a marker of the disease activity. However, currently this method is not widely used in clinical practice. In the presented study, the relationship between lesions (T2) in magnetic resonance imaging (MRI), including contrast-enhancing (Gd+), clinical relapses and no evidence of disease activity (NEDA-3) with volumetric changes was investigated.MethodsClinical and MRI data from RRMS patients treated with cladribine tablets (CLAD) and alemtuzumab (ALEM) were retrospectively analyzed at 4 time points (pretreatment and 3 years of follow-up). Volumetric data were obtained using the FreeSurfer. Annual volumetric changes and new T2/Gd + lesions were pooled together to assess short-term relationships, baseline T2/Gd + lesions were correlated with 3-year volume changes and years with NEDA-3 and without NEDA-3 were compared.ResultsThe study included 33 patients treated with CLAD and 19 patients treated with ALEM. In the year-to-year analysis (nCLAD = 59, nALEM = 36) within the CLAD group, new T2 lesions were significantly associated with a decrease in thalamic (p = 0.02), cerebellum (p = 0.05) and deep grey matter (p = 0.05) volume. When analyzing the correlation between baseline T2 lesions and overall 3-year volume changes (NCLAD = 9, NALEM = 7), in the CLAD group, strong associations were found with whole brain (p = 0.001, ꞵ = −0.89), cerebellum (p = 0.002, ꞵ = −0.20), cerebellar cortex (p = 0.003, ꞵ = −0.19) and DGM (p = 0.015, ꞵ = −0.04) atrophy, as well as with lateral ventricular volume increase (p = 0.00001, ꞵ = 0.1). A similar situation occurred when only the first year of treatment was analyzed (NCLAD = 29, NALEM = 13). It was not observed in the ALEM group. Interestingly, no correlation was noted between Gd + lesions and volumetric changes. Remarkably, no statistically significant differences between years with and without relapses were observed. However, years without NEDA-3 (n = 31) were characterized by greater atrophy in white matter (p = 0.04), thalamus (p = 0.02), and putamen (p = 0.04).ConclusionThe results of the presented study suggested an association of increased brain atrophy with radiological activity rather than with relapsing disease activity. However, further studies with larger numbers of patients are needed to verify these associations more precisely.